Domestic visitors' travel intention to Sabah post COVID-19 travel restriction / Michelina David, Tania Maria Tangit and Spencer Hedley Mogindol - David, Michelina; Tangit, Tania Maria; Mogindol, Spencer Hedley (2023)
This study aimed to study the intentions of Malaysian domestic travellers to visit Sabah after the COVID-19 travel restrictions were lifted by exploring the variables of fear of COVID-19, travel anxiety, subjective norm, perceived behavioural control, and risk attitude. This study utilizes the Theory of Planned Behaviour (TPB) to explore factors impacting travel intentions in a post-pandemic context. SPSS and Partial Least Squares Structural Equation Modelling (PLS-SEM) were used to analyse the 303 online survey respondents. The study reveals diverse perceptions among Malaysian domestic visitors regarding travel to Sabah after COVID-19 travel restrictions. Fear of COVID-19 and risk attitude were found to have no significant impact on travel intentions. However, perceived behavioural control, subjective norms, and travel anxiety showed significant relationships with travel intention. The findings offer practical implications for tourism stakeholders to develop targeted strategies for attracting and accommodating domestic travellers in Sabah while contributing to existing knowledge in the tourism and educational field. This study incorporated the TPB model by adding more variables, resulting in a more powerful explanation of post-pandemic travel intentions.